Edukasi Dan Peningkatan Literasi Digital Dalam Upaya Menanggulangi Hoaks Dan Judi Online Pada Remaja SMKN 1 Plupuh Sragen - Dani, Jeratallah Aram; Setiawan, Ali Arif; Syaifullah, Jahid (Bengawan : Jurnal Pengabdian Masyarakat, 2024)
The development of communication media and information technology, coupled with the freedom to express opinions, has made teenagers increasingly show an image of themselves that is more open to any information they receive on the internet and various social media. Openness to receiving excessive information without a complete understanding of the information makes the flow of information subject to many interpretations. When faced with various types of information from the media, most teenagers become confused about which information is useful and which is not. In this phenomenon, media literacy knowledge is really needed as capital so that communicants as media users can classify and evaluate media content sharply and thoroughly and consume it according to their needs. This community service program targeting vocational school youth in the Plupuh Sragen area uses the participation method, with a lecture and discussion model where the target participants also play an active role in finding and completing findings in an effort to prevent hoaxes and online gambling. A total of 40 teenagers who are members of SMKN 1 Plupuh Sragen took part in a series of outreach events with basic literacy material, information verification techniques, tools and applications for checking facts, and internet ethics.